MORPHOFUNCTIONAL FEATURES OF RAT TESTES INTERSTITIAL ENDOCRINOCYTES AND SUSTENTOCYTES AFTER 90 DAYS OF CENTRAL TESTOSTERONE SYNTHESIS DEPRIVATION - Stetsuk, Ye.V.; Akimov, O.Ye.; Shepitko, K.V.; Goltsev, A.N. (World of Medicine and Biology, 2020)
With the social system development, there is a tendency to change attitudes towards family and family values. In developed European countries, there is a trend towards high sexual activity in elderly men and late creation of a family with children, which undergoes certain difficulties in connection with a decreased testosterone production in later years. The purpose of the study was to establish the microscopic organization of rat interstitial endocrinocytes and sustentocytes, to determine the sources of nitric oxide production and the intensity of oxidative stress in the testes with experimental central deprivation of testosterone synthesis with diphereline on the 90th day of the experiment. The experiments were carried out on 20 sexually mature male white rats of the Wistar line. Rats were divided into 2 groups: the control group (10) and the experimental group (10), which were injected subcutaneously with diphereline (Triptorelin embonate) at a dose of 0.3 mg / kg of the active substance for 90 days. Prolonged central deprivation of testosterone synthesis in animals leads to emergence of functional stress structural signs in population of sustentocytes and interstitial endocrinocytes, which are aimed to support testicular secretion. Central deprivation of testosterone synthesis within 90 days causes oxidative stress development owing to reactive oxygen species hyperproduction and nitrite accumulation in testicular tissue due to increased inducible NO-synthase activity.